2004
DOI: 10.1038/sj.onc.1208140
|View full text |Cite
|
Sign up to set email alerts
|

The erythropoietin-receptor pathway modulates survival of cancer cells

Abstract: Anemia in cancer patients is associated with reduced quality of life and local failure after radiation treatment. However, the use of erythropoietin to correct cancer anemia and to improve radiation efficacy was disappointing. Erythropoietin-receptor signaling mainly acts via activation of STAT 5, but also crossactivates the antiapoptotic transcription factor NF-jB. This causes neuroprotection against oxidative stress and implies radioprotection. In order to investigate possible radioprotective effects of eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
0
37
0
2
Order By: Relevance
“…EPO/EPOR expressing cancers include breast cancer, cervical carcinoma, melanoma, neuroblastomas and glioblastomas (Acs et al, 2001(Acs et al, , 2002(Acs et al, , 2003Arcasoy et al, 2002;Yasuda et al, 2003). Although prior studies focused primarily upon the expression of EPO and EPOR in selected tumor types, some reports suggested a role for EPO in the proliferation and survival of cancer cells (Acs et al, 2001;Arcasoy et al, 2002;Yasuda et al, 2003;Pajonk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…EPO/EPOR expressing cancers include breast cancer, cervical carcinoma, melanoma, neuroblastomas and glioblastomas (Acs et al, 2001(Acs et al, , 2002(Acs et al, , 2003Arcasoy et al, 2002;Yasuda et al, 2003). Although prior studies focused primarily upon the expression of EPO and EPOR in selected tumor types, some reports suggested a role for EPO in the proliferation and survival of cancer cells (Acs et al, 2001;Arcasoy et al, 2002;Yasuda et al, 2003;Pajonk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies are needed with more specific antibodies and greater sample numbers to determine the prognostic significance of EpoR expression on tumors. The biological effects of Epo stimulation of tumor cells is still debated with reports of enhanced survival (8,11), proliferation (4,6,(38)(39)(40), resistance to treatment (38,41,42), tumor angiogenesis (43)(44)(45), chemotaxis (46), invasion (47)(48)(49)(50), and migration (40,46,51). Others have reported no discernible effects of Epo (52).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are a large number of studies that find that ESAs do not stimulate tumour progression in preclinical models (reviewed by Osterborg et al, 2007;Sinclair et al, 2007). Since specific anti-EpoR antibodies have yet to be identified, we investigated if EpoR was overexpressed in tumours by performing a systematic analysis of EPOR genomic amplification and transcription in more than 15 different primary tumour types, and EpoR transcript and surface EpoR expression analysis in representative tumour cell lines in which rHuEpo has been reported to induce responses (Westenfelder and Baranowski, 2000;Acs et al, 2001Acs et al, , 2003Pajonk et al, 2004;Um et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The particular cell lines used in this study were selected because of reports that they responded to Epo. The six cell lines included megakaryoblastic leukaemia line UT7/Epo cells (known to be Epo responsive; Laugsch et al, 2008) as a positive control; a renal carcinoma line 769P (with extremely low levels of EpoR mRNA) (Elliott et al, 2006) as a negative control; and four cell lines in which rHuEpo has been reported to induce an in vitro response: breast carcinoma line MCF-7 (Acs et al, 2001), cervical carcinoma line HeLa (Acs et al, 2003;Pajonk et al, 2004), renal carcinoma line CAKI-2 (Westenfelder and Baranowski, 2000), and neuroblastoma line SHSY-5Y (Um et al, 2007). Relatively high levels of EPOR transcripts were observed in UT7/Epo cells, very low levels in MCF-7, HeLa, SHSY-5Y, and CAKI-2 cells, and negligible levels in 769P cells ( Figure 5A).…”
Section: Epor Transcript Levels and Surface Expression In Tumour Cellmentioning
confidence: 99%